2018
DOI: 10.1177/0022034518774331
|View full text |Cite
|
Sign up to set email alerts
|

Water Fluoridation and Dental Caries in U.S. Children and Adolescents

Abstract: This cross-sectional study sought to evaluate associations between availability of community water fluoridation (CWF) and dental caries experience in the U.S. child and adolescent population. County-level estimates of the percentage of population served by CWF (% CWF) from the Centers for Disease Control and Prevention's Water Fluoridation Reporting System were merged with dental examination data from 10 y of National Health and Nutrition Examination Surveys (1999 to 2004 and 2011 to 2014). Dental caries exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 17 publications
1
82
0
6
Order By: Relevance
“…One of the reasons for dental caries to affect the quality of life is painful sensition [16][17] . Toothache leads to limitations in the oral functioning and emotional state of the child 18 , causing difficulty to relax and problems in school performance 19 , as well as difficulty sleeping 16 . In our study, older children presented the higher means of ECOHIS, corroborating previous studies 6,11 .…”
mentioning
confidence: 99%
“…One of the reasons for dental caries to affect the quality of life is painful sensition [16][17] . Toothache leads to limitations in the oral functioning and emotional state of the child 18 , causing difficulty to relax and problems in school performance 19 , as well as difficulty sleeping 16 . In our study, older children presented the higher means of ECOHIS, corroborating previous studies 6,11 .…”
mentioning
confidence: 99%
“…Children with a high dmft scores were more likely to have gone to the dentist for other reasons than preventive care. Previous studies have demonstrated that higher dmft scores could increase the probability of a painful event occurring . Therefore, this could reflect the need to visit the dentist for treatment reasons, since pain is one of the main reasons for seeking dental health services…”
Section: Discussionmentioning
confidence: 99%
“…As dores dentais podem ser originadas dos tecidos inervados do dente ou circundantes ao mesmo (Slade, 2001). Diversos fatores podem ser responsáveis pela sensação dolorosa nesta região, como a esfoliação dental, traumatismos dentários, doenças gengivais e a cárie dentária (Slade, 2001;Peres et al, 2005;Bastos et al, 2007;Boeira et al, 2012).…”
Section: Lista De Tabelasunclassified
“…Diversos fatores podem ser responsáveis pela sensação dolorosa nesta região, como a esfoliação dental, traumatismos dentários, doenças gengivais e a cárie dentária (Slade, 2001;Peres et al, 2005;Bastos et al, 2007;Boeira et al, 2012). Em crianças, a maior ocorrência de dor de dente ocorre devido a cárie dentária (Boeira et al, 2012), que é uma doença crônica de elevada prevalência durante a infância (Organização Mundial de Saúde -OMS, 2012) e que possui um caráter multifatorial, podendo estar associada a fatores biológicos, comportamentais e socioeconômicos, (Fejerskov e Kidd, 2005;Selwits et al, 2007) dentre eles a presença de biofilme cariogênico, características salivares (capacidade tampão, pH e fluxo), consumo de açúcares (Shanmugam et al, 2013;Cunha-Cruz et al, 2013), renda e acesso ao serviço odontológico (Peres et al, 2000;Galindo et al, 2005;Noro et al, 2009;Lopes et al, 2013).…”
Section: Lista De Tabelasunclassified
See 1 more Smart Citation